Mechanisms and Factors Controlling Photoisomerization Equilibria, Ligand Exchange, and Water Oxidation Catalysis Capabilities of Mononuclear Ruthenium(II) Complexes. Issue 23 (17th July 2015) - Hirahara, Masanari; Hakamata, Tomoya; League, Aaron B.; Ertem, Mehmed Z.; Takahashi, Kosuke; Nagai, Sho; Inaba, Keisuke; Yamazaki, Hirosato; Saito, Kenji; Yui, Tatsuto; Cramer, Christopher J.; Yagi, Masayuki
Abstract: The photoisomerization equilibrium between distal ‐ and proximal ‐[Ru(tpy)(pyqu)OH2 ] 2+ [ d ‐ and p ‐RuH2 O, tpy = 2, 2′;6′, 2″‐terpyridine, pyqu = 2‐(2′‐pyridyl)quinoline] is characterized. The kinetic analysis of the pD‐dependent photoisomerization reactions (monitored by 1 H NMR) of d ‐RuH2 O and p ‐RuH2 O shows (1) that both hydroxo isomers, distal ‐ and proximal ‐[Ru(tpy)(pyqu)OH] +, are inert to photoisomerization, and (2) that the back reaction ( distal to proximal ) is 3.0 times faster than the forward reaction ( proximal to distal ). Isolation of distal ‐ and proximal ‐[Ru(tpy)(pyqu)Cl] + ( d ‐ and p ‐RuCl) as well as d ‐ and p ‐RuH2 O isomers enabled comprehensive studies on geometric structures, ligand exchange and redox reactions, and water oxidation catalysis for these isomers. The observed aquation rate constant (9.2 × 10 –2  s –1 at 40 μM ) of p ‐RuCl to form p ‐RuH2 O is 1700 times higher than that (5.4 × 10 –5  s –1 at 63 μM ) of d ‐ RuCl at 298 K owing to the steric repulsion between a chloro ligand and the 8‐proton of the quinoline moiety. The turnover frequency (TOF = 1.7 × 10 –3  s –1 ) of p ‐RuH2 O for catalytic water oxidation is 1.7 times greater than that (1.0 × 10 –3  s –1 ) for d ‐RuH2 O, in contrast to the [Ru(tpy)(pynp)OH2 ] 2+ isomer system, in which the TOF of the distal isomer is higher than that of the proximal one by one order of magnitude. The mechanisms and factors controlling the photoisomerization equilibria and water oxidation catalysis of the d ‐ and p ‐RuH2 O isomers are discussed on the basis of experimental and theoretical investigations. Abstract : The photoisomerization equilibrium between distal ‐ and proximal ‐[Ru(tpy)(pyqu)OH2 ] 2+ [ d ‐ and p ‐RuH2 O, tpy = 2, 2′, 6′, 2″‐terpyridine, pyqu = 2‐(2‐pyridyl)quinoline] is illustrated. Isolation of distal ‐ and proximal ‐[Ru(tpy)(pyqu)Cl] + and d ‐ and p ‐RuH2 O isomers enabled comprehensive studies on geometric structures, ligand exchange and redox reactions, and water oxidation catalysis for these isomers.